The Onset of Lactation among Postpartum Mothers at Private Midwifery Practice - Dwilda Ferdinandus, Euvanggelia; Dwi Jayanti, Ratna; Piesesha, Frieska; Zada Fauziyah, Nail Firah; Giyanti Putri, Pionera Seconda (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The onset of lactation is the beginning of the breastfeeding process, marked by breast tenderness and the release of colostrum, which occurs ≤72 hours after delivery. Objective: This study aims to explore the onset of lactation in postpartum mothers at Private Midwifery Practices. Method: The study used a descriptive study method involving 83 postpartum mothers in 5 independent midwife practices in Surabaya. Statistical analysis used descriptive statistics through frequency distribution. Result and Discussion: Most postpartum mothers were in the reproductive age group (85.5%) and multiparous (73.5%). However, most postpartum mothers did not engage in Early Initiation of Breastfeeding immediately after giving birth (92.8%). Seventy-three percent of mothers had moderate knowledge about lactation, and 80.7% experienced a rapid onset of lactation. Conclusion: The onset of lactation is an important part that determines the success of breastfeeding to meet the nutritional needs of the baby